XIAP-mediated rescue of ischemic neural rat retina from death - Renwick, Joanna (University of Ottawa (Canada), 2004)
XIAP-mediated gene therapy has been shown to protect brain neurons from ischemic cell death. However, it has not been shown whether XIAP can protect retinal neurons as well. To determine this, an acute retinal ischemia rat model was utilized. Eyes were injected with AAV-XIAP or AAV-GFP and, six weeks later, rendered ischemic by raising intraocular pressure to 110 mmHg and maintaining the pressure for one hour. Retinas were analyzed both functionally and structurally at various time points following ischemia. Functional analysis shows that XIAP, when overexpressed, rescues retinal neurons up to 4 weeks post-ischemia (wpi). Structural rescue is also evident from cell counts of H+E stained retinas. There are also significantly less TUNEL positive cells in the inner nuclear layer of the XIAP-treated retinas at 24 hpi. Therefore, XIAP-mediated gene therapy appears to functionally and structurally rescue retinal neurons from death following a transient ischemic episode.
Keywords: Health Sciences, Medicine and Surgery.